2009
DOI: 10.1002/art.24524
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale analysis of association between GDF5 and FRZB variants and osteoarthritis of the hip, knee, and hand

Abstract: Objective GDF5 and FRZB have been proposed as genetic loci conferring susceptibility to osteoarthritis (OA); however, the results of several studies investigating the association of OA with the rs143383 polymorphism of the GDF5 gene or the rs7775 and rs288326 polymorphisms of the FRZB gene have been conflicting or inconclusive. To examine these associations, we performed a large-scale meta-analysis of individual-level data. Methods Fourteen teams contributed data on polymorphisms and knee, hip, and hand OA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(156 citation statements)
references
References 48 publications
(68 reference statements)
4
148
0
2
Order By: Relevance
“…What is interesting in this respect is the fact that genes that are mainly active in skeletal development, such as FRZB and GDF5, are identified as OA susceptibility genes (5,6). These genes are involved in the orchestration of growth plate chondrocytes that results in formation of cartilage and eventually bone during endochondral ossification (7).…”
mentioning
confidence: 99%
“…What is interesting in this respect is the fact that genes that are mainly active in skeletal development, such as FRZB and GDF5, are identified as OA susceptibility genes (5,6). These genes are involved in the orchestration of growth plate chondrocytes that results in formation of cartilage and eventually bone during endochondral ossification (7).…”
mentioning
confidence: 99%
“…35 The associations reported in the original paper were marginal. 36 When multiple testing is considered, only a negative association has been reported in replication studies, even in the European Caucasians.…”
Section: Gdf5mentioning
confidence: 97%
“…In a large-scale meta-analysis using 3500-5800 cases and 5200-10 800 controls, collected by 14 research groups in the Western Europe and East Asia, Evangelou et al 35 examined the association of OA with three SNPs in previously reported genes, rs143383 in GDF5 together with rs7775 and rs288326 in FRZB. A significant association for rs143383 with knee OA without significant betweenstudy heterogeneity, were identified (P¼9.4Â10 À7 ).…”
Section: Gdf5mentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Polymorphisms in FRZB have been associated with hip osteoarthritis although the effect is not consistent over different groups. 33,34 Frzb − / − mice show increased susceptibility to cartilage damage in induced models of osteoarthritis. 35 We could associate this observation with increased Wnt signaling and destructive enzyme expression within the articular cartilage but also with abnormalities in bone.…”
Section: Progress In Genetics Identifies a Key Role For Developmentalmentioning
confidence: 99%